Exploring Farmers’ Awareness and Key Determinants of Electric Fencing Adoption in Jerantut, Pahang. - Hamzah, Nur Masriyah; Abd Latif, Amirul Afiq; Kassim, Nur Qursyna Boll; Mohd Khairlani, Nurul Hidayah (Journal of Islamic, Social, Economics and Development, 2025)
Farmers often encounter challenges when their crops, especially fruit trees, begin to bear fruit. They face significant threats from mammals like cattle, monkeys, and squirrels that feed on fruits. This impacts their financial costs due to early-season losses and necessitates effective mitigation strategies. Consequently, many farmers have turned to electric fencing to protect their crops from mammalian attacks. A study conducted among farmers in Jerantut, Pahang, surveyed 42 respondents to assess their awareness and adoption of electric fencing. It found that farmers in the region displayed a high awareness of electric fencing as a solution to mitigate mammal-related crop damage. The study identified several influential factors affecting the adoption of electric fencing, including geographical location, promotion by extension agents, peer reviews, and environmental benefits. Statistical analyses revealed strong positive correlations between farmers' awareness of electric fencing benefits, environmental concerns, and promotional efforts from agricultural extension services and agribusiness companies. These findings underscore the importance of targeted interventions by policymakers and agricultural educators to enhance the adoption of electric fencing among smallholder farmers, particularly in rural areas. Future research should further investigate the efficacy of electric fencing in improving crop production and reducing mammalian threats in agricultural settings, aiming to support sustainable farming practices and enhance overall agricultural productivity.